A Protective Role of NOD2 on Oxazolone-induced Intestinal Inflammation Through IL-1β-mediated Signalling Pathway. (2nd August 2022) - Secher, Thomas; Couturier, Aurélie; Huot, Ludovic; Bouscayrol, Helene; Grandjean, Teddy; Boulard, Olivier; Hot, David; Ryffel, Bernhard; Chamaillard, Mathias
Abstract: Background and Aims: NOD2 has emerged as a critical player in the induction of both Th1 and Th2 responses for potentiation and polarisation of antigen-dependent immunity. Loss-of-function mutations in the NOD2-encoding gene and deregulation of its downstream signalling pathway have been linked to Crohn's disease. Although it is well documented that NOD2 is capable of sensing bacterial muramyl dipeptide, it remains counter-intuitive to link development of overt intestinal inflammation to a loss of bacterial-induced inflammatory response. We hypothesised that a T helper bias could also contribute to an autoimmune-like colitis different from inflammation that is fully fledged by Th1 type cells. Methods: An oedematous bowel wall with a mixed Th1/Th2 response was induced in mice by intrarectal instillation of the haptenating agent oxazolone. Survival and clinical scoring were evaluated. At several time points after instillation, colonic damage was assessed by macroscopic and microscopic observations. To evaluate the involvement of NOD2 in immunochemical phenomena, quantitative polymerase chain reaction [PCR] and flow cytometry analysis were performed. Bone marrow chimera experimentation allowed us to evaluate the role of haematopoietic/non-hematopoietic NOD2-expressing cells. Results: Herein, we identified a key regulatory circuit whereby NOD2-mediated sensing of a muramyl dipeptide [MDP] by radio-resistant cells improves colitis with a mixed Th1/Th2 response that is induced by oxazolone. Genetic ablation of either Nod2 or Ripk2 precipitated oxazolone colitis that is predominantly linked to a lack of interferon-gamma. Bone marrow chimera experiments revealed that inactivation of Nod2 signalling in non-haematopoietic cells is causing a biased M1-M2 polarisation of macrophages and a decreased frequency of splenic regulatory T cells that correlates with an impaired activation of CD4  +  T cells within mesenteric lymph nodes. Mechanistically, mice were protected from oxazolone-induced colitis upon administration of MDP in an interleukin-1- and interleukin-23-dependent manner. Conclusions: These findings indicate that Nod2 signalling may prevent pathological conversion of T helper cells for maintenance of tissue homeostasis.